Utilization of SIKADU on Quality of Service of Academic Information Systems - Arwani, Agus (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
The service quality and Integrated Academic Information System Skill to moderate the relationship between Sikadu use and service quality. The purpose of this study is to determine the effect of information systems on service quality and decrease the use of information systems. This research method uses field research methods with quantitative approaches. This study student, lecturers, and teaching staff program from FEBI IAIN Pekalongan and sampling methods with Non-Probability Sampling with accidental sampling techniques. The results of the study obtained Information System Quality has a significant favorable influence on service quality. It shows that the quality of information quality system can improve service quality. The variety of information systems moderates the effect of using utilization on service quality, so it can conclude that the Sikadu utility variable includes moderating variables. It shows that quality information systems influence the use of technology on service quality.